KubeZTs: uma implementação Zero Trust para o Kubernetes - Silva, Guilherme Egle Pegado Lima (2024)
The use of Kubernetes as a platform for containerized application deployment and management has increased dramatically in recent years. To preserve sensitive data and the integrity of programs, new security issues have been brought about by this widespread usage, which must be resolved. The Kubernetes Zero Trust Scanner (KubeZTs), a unique tool created to confirm that Kubernetes cluster configurations adhere to the Zero Trust paradigm's tenets, is presented in this work. The Zero Trust paradigm necessitates ongoing security measure verification and highlights the need of assuming no implicit trust within a network. A collection of Python scripts is used in the tool's implementation to communicate with the Kubernetes API and carry out a number of security tests.